The Practice of Infant Sleep Position among Mothers in Jimma Town Public Health Institutions, Jimma, Oromia, South West Ethiopia, 2022 - Aynalem Yetwale; Bilen Tigstu; Tsegaw Biyazin; Belete Fenta; Yalemtsehay Dagnaw; Yaregal Dessalew (SAGE Publishing, 2023)
Background One of the important interventions in the infantile period is the selection of appropriate infant sleeping position. Unsafe infant sleep position is associated with sudden unexpected death in infancy. Yet, little is known about the practice of infant sleep position in Ethiopia. This study aimed to assess the practice of infant sleep position among mothers attending mother and child health service in Jimma town public health institutions, South West Ethiopia, 2022. Methods An institutional based cross-sectional study design was conducted on 409 women attending Maternal and child health service in Jimma town public health facilities. The data were collected using a pre-tested and semi- structured questionnaire. Binary Logistic regression was used to analyze the association between the practice infant sleeping positions and explanatory variables. The strength of association was evaluated using an odds ratio at a 95% confidence interval and a P -value ≤ .05 was considered to declare significant associations. Results Four hundred nine women participated in the study, with a response rate of 97%. The practice of recommended infant sleeping position (supine position) in this study was 33.5% [95% CI (28.9% - 38.6%)]. Being married Adjusted odds ratio (AOR) 2.6; 95% CI (1.04-6.48)), residence (AOR 1.88; 95% CI (1.1-3.31)) multi gravidity (AOR 1.6; 95% CI (1.02-2.59)) and having good knowledge of sleeping position (AOR 1.55; 95% CI (1.01-2.38)) were significantly associated with the practice of infant sleep position Conclusion The practice of medically recommended infant sleep position in this study was low. Being married, residence, multi gravidity and having good knowledge of sleeping position were significantly associated with the practice of infant sleep position. Therefore, considering these associated factors during health care provision and disseminating information on safe sleep practices for mothers is needed. Also, different stakeholders, including the federal ministry of health, health professionals, and health institutions at different levels, need to give attention to such problems in addition to the service to reduce infant mortality